The Effect of Balance, Mindfulness, and Combined Exercises on Psychological Well-being and Fear of Falling in Inactive Elderly - Armin Farokhi; Ali Yaghobian; Mahdi Najafian Razavi; Amir Moghadam (Biyumikānīk-i varzishī)
Objective The high prevalence of falls among the elderly leads to significant adverse health consequences, including reduced quality of life and functional limitations. The primary aim of this study was to examine the effects of mindfulness, balance, and combined exercises on psychological well-being and fear of falling in inactive elderly individuals. Methods The subjects of this research were 48 elderly men aged 65 to 75 years, who were selected voluntarily based on the study's objectives from among the elderly men in Mashhad, Iran. They were randomly assigned to one of four groups (n=12): (1) Mindfulness Practice Group, (2) Balance Practice Group, (3) Combined Practice Group, and (4) Control Group. The research employed a semi-experimental design with pre-test and post-test assessments. Participants first completed the Fall Efficacy Questionnaire and the Psychological Well-being Scale as a pre-test. Subsequently, those in the intervention groups participated in balance exercises, mindfulness exercises, or combined exercises for 16 sessions, each lasting 60 minutes (three times a week), according to their group's protocol. Results The findings indicated a significant difference in the effects of mindfulness, balance, and combined exercises on psychological well-being and fear of falling in inactive elderly individuals (p<0.001). Conclusion All three interventions—balance exercises, mindfulness exercises, and combined exercises—were effective in improving psychological well-being and reducing the fear of falling among inactive elderly individuals. Notably, the combined exercise method (balance and mindfulness) had a greater impact on psychological well-being and fear of falling compared to the other methods.